Liberating language education - Lytra, Vally; Ros i Solé, Cristina; Anderson, Jim 1950-; Macleroy, Vicky (Multilingual Matters, 2022)
This book engages with new ways of understanding language that include other resources and practices and bring to the fore its messiness, unpredictability and interconnectedness. The chapters illustrate how a translingual and transcultural orientation to language can provide a point of entry to reimagining language education in the 21st century
Keywords: Bilingualism & multilingualism; LANGUAGE TEACHING & LEARNING (OTHER THAN ELT); Sociolinguistics; LANGUAGE ARTS & DISCIPLINES / Study & Teaching; Language and education; Languages, Modern -- Study and teaching; Multilingual education